Perancangan Sistem Informasi Administrasi Keuangan Berbasis Android Menggunakan Kodular (Studi Kasus: Senat Mahasiswa Fakultas Teknik UAJ) - Surbakti, Feliks Prasepta Sejahtera; Kane, Evan (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
The Student Senate of the Faculty of Engineering, Atma Jaya Catholic University is one of the organizations affected by the pandemic, so they carry out semi-manual work processes, meaning that most of the processes are already using digital systems. Activities that are not integrated raises new problems such as non-recorded transactions, inaccurate financial report calculation results, and the length of time needed for treasurers to manage financial administration. Because of these constraints, research was conducted on the design and construction of the SMFT UAJ information system related to the financial administration process. In the process of designing the SMFT UAJ financial administration information system, the System Development Life Cycle Waterfall method was used as a reference for making the system with the help of the Kodular tool in building the entire system using the block coding system and the google sheet database. System testing is carried out in 2 stages, namely system testing and acceptance testing on 4 aspects (learnability, efficiency, memorability, and satisfaction). The test results show that this system is feasible for use by SMFT UAJ with the result of reducing processing time for learnability and memorability tests. The resulting efficiency test was 0.0143/second, and the SUS value was 92.5. Keywords: Financial Information System, Kodular, SMFT UAJ